Donepezil 23 mg in Asian patients with moderate‐to‐severe Alzheimer's disease. (29th February 2016) - Han, S. ‐H.; Lee, J. ‐H.; Kim, S. Y.; Park, K. W.; Chen, C.; Tripathi, M.; Dash, A.; Kubota, N.
Abstract : Background: Ethnic diversity between different populations may affect treatment safety and efficacy. Aims and methods: A subanalysis to a global trial (study 326) was carried out to ascertain the safety and efficacy of donepezil 23 mg/day compared with donepezil 10 mg/day in Asian patients with moderate‐to‐severe Alzheimer's disease. Changes in cognition and global functioning were measured by the Severe Impairment Battery (SIB) and Clinician's Interview‐Based Impression of Change Plus Caregiver Input (CIBIC‐Plus), respectively, at week 24. Results: Cognitive improvement measured by SIB score was greater with donepezil 23 mg than with donepezil 10 mg (+1.36 vs −1.56]; difference, 2.92). There was no difference between the groups in global function measured by the CIBIC‐Plus (3.94 and 3.95, respectively). Overall, 119 patients (82.1%) receiving donepezil 23 mg and 56 (71.8%) receiving donepezil 10 mg experienced ≥1 treatment emergent adverse events (TEAEs). In the donepezil 23 mg group, the incidence of TEAEs was higher among patients of lower weight (<55 kg) at baseline than in those of higher weight (64 of 75 patients [85.3%] vs 55 of 70 patients [78.5%]). Conclusions: The benefits and risks associated with donepezil 23 mg in Asian patients are comparable to those of the global study population.